Pogledi na ritualnost in ritualne prakse na Slovenskem - Fikfak, Jurij (Traditiones (Ljubljana), 2008)
This article analyzes some of the most characteristic perspectives on ritualism and ritual practices in Slovenia in the past two centuries. Special focus is placed on researchers studying rituals and their orientations, focuses, and argumentation. It raises the question of which strata of the population were included in studies and which emphases in these studies were the most important.
Keywords: ethnology; etnologija; folkloristics; folkloristika; history; zgodovina; ljudske šege; rituali; metodologija; Slovenia; Slovenija